BACTERIOLOGICAL FINDINGS IN THE MATERIAL CULTURE OF ENDOMETRIAL - Sáenz Loayza, Saturnino (2015)
In this paper the bacteriological research was conducted on 104 samples of material obtained through the endometrial curettage obstetric gynecology different reasons, as many women who were hospitalized in the gynecology obstetrics services HMC: Incomplete Abortion, septic abortion, post extraction IUD, LUB and postpartum endometritis. Each endometrial sample obtained in strictly aseptic conditions, was indicted in the service of the Department of Bacteriology Laboratory. Cultivation and respective microscopic examination. positive culture was found in 44%. Bacteriological impact found in the following order: Staphylococcus coagulase negative 15.3%; E. coli 11.5%, 10.1% mixed flora, while in most of them present E. coli; Staphylococcus coagulase positive 2.8%; Alpha hemolytic streptococcus 0.9%; Citrobacter freundi 0.9%; Citrobacter specie Specie 0.9% and 0.9% Alcaligenes. The average age of the patients who had positive culture was 29.63 years ± 7.08 SD, and as regards parity was at 3. The endometrial cavity under physiological conditions is free of demonstrable microorganisms. In obstetric gynecology clinical circumstances as described, allow bacterial colonization that allow find a significant impact as grounds for gynecological septic conditions. No anaerobes were studied.